sen(nx)

sin(2x) = 2cos(x) sin(x)
sin(3x) = –sin3(x)+3cos2(x) sin(x)
sin(4x) = –4cos x) sin3(x)+4cos3(x) sin(x)
sin(5x) = sin5(x)–10cos2(x) sin3(x)+5cos4(x) sin(x)
sin(6x) = 6cos(x) sin5(x)–20cos3(x) sin3(x)+6cos5(x) sin(x)
sin(7x) = –sin7(x)+21cos2(x) sin5(x)–35cos4(x) sin3(x)+7cos6(x) sin(x)
sin(8x) = –8cos(x) sin7(x)+56cos3(x) sin5(x)–56cos5(x) sin3(x)+8cos7(x) sin(x)
sin(9x) = sin9(x)–36cos2(x) sin7(x)+126cos4(x) sin5(x)–84cos6(x) sin3(x)+9cos8(x) sin(x)
sin(10x) = 10cos(x) sin9(x)–120cos3(x) sin7(x)+252cos5(x) sin5(x)–120cos7(x) sin3(x)+10cos9(x) sin(x)

 

Lascia un commento

Il tuo indirizzo email non sarà pubblicato.

Time limit is exhausted. Please reload CAPTCHA.